Correlation between early corneal edema and endothelial cell loss after phacoemulsification cataract surgery - Chen, Si; Li, Xiaoqing; Huang, Li; Feng, Qin; Lu, Huilong; Mu, Jing (Frontiers in Medicine, 2025)
PurposeThis study aimed to investigate the correlation between early corneal edema and loss of corneal endothelial cells after phacoemulsification.MethodsThe corneal condition of each operated eye was observed using slit-lamp biomicroscopy at different time points, and the clinical score of corneal edema was determined. Central corneal thickness (CCT) and endothelial cell density (ECD) of each operative eye were measured by corneal endothelial microscopy at different time points.ResultsThere were 10 male (41.67%) and 14 female (58.33%) cataract patients with a mean age of aged 71.88 ± 10.14 years. The clinical score of corneal edema grade in cataract patients on the first postoperative day (1.79 ± 1.10) was significantly higher than that before surgery (0.0 ± 0.0) (p < 0.0001). Similarly, the CCT on first postoperative day (566.08 ± 32.73 μm) was significantly higher than that before surgery (530.71 ± 24.42 μm) (p < 0.0001). In addition, compared with the preoperative ECD (2,841 ± 502 cells/mm2), the ECD (1,993 ± 744 cells/mm2) 1 month after surgery (M1) decreased significantly (p < 0.0001), and the percentage of endothelial cell loss was 30.45 ± 20.23%. Moreover, both the corneal edema grade (Spearman’s r = 0.7811, p < 0.0001) and CCT (Spearman’s r = 0.7191, p < 0.0001) on the first day after surgery were significantly correlated with the loss of corneal endothelial cells 1 month postoperative day.ConclusionEarly corneal edema after cataract surgery is closely associated with the loss of central corneal endothelial cells. Therefore, the grade of corneal edema and CCT on the first day after cataract surgery can be used as effective indices for predicting the effects of phacoemulsification on corneal endothelial cells.